Unreasonable Discrimination Against Air Travel Passengers - Leah H. Kim (Washington University Journal of Law & Policy, 2017)
This Note discusses the current hurdles imposed by 49 U.S.C. § 41310, the Discriminatory Statute 41310, caused by its failure to define “unreasonable discrimination” in air transpiration and reports filed with the Department of Transportation (DOT), particularly by ethnic and religious minorities. Kim proposes a preliminary test the DOT may use in evaluating “unreasonable discrimination” in air transportation. The author also evaluates whether protections for employment under Discriminatory Statute 40127 are exclusive to certain enumerated classifications, in light a circuit split. The Note concludes establishing some guidelines for “unreasonable discrimination” would help the airline industry by decreasing meritless claims, increasing the ability to identify actionable claims, and guidance for industry practices to prevent discriminatory conduct.
Keywords: Discrimination; Travel; Race; Ethnicity; Religion; DOT; TSA; Claims